2005
DOI: 10.1002/cne.20495
|View full text |Cite
|
Sign up to set email alerts
|

Regional abnormalities in retinal development are associated with local ocular hypopigmentation

Abstract: The retinal pigment epithelium (RPE) plays a key role in regulating retinal development. The critical enzyme in pigment production is tyrosinase. Transgenic mice with a tyrosinase construct where the locus control region was deleted (YRT4) display a variegated phenotype of tyrosinase expression. Their central retina is largely pigment free, whereas more peripheral regions are heavily pigmented. We have used this model to ask whether the influence of pigmented RPE over the retina during development is fundament… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 54 publications
1
19
0
Order By: Relevance
“…This phenotype is associated with mutations in melanin production or melanosome biogenesis and turnover, and leads to decussation defects and mistargeting (Rice et al, 1995, Herrera et al, 2003, Rebsam et al, 2012, Bhansali et al, 2014, Jeffery, 2001). Birthdating experiments have suggested that this is due to a delay in the generation of RGCs in albino compared with pigmented retina (Bhansali et al, 2014, Drager, 1985, Gimenez et al, 2005, Lavado et al, 2006, Rachel et al, 2002). Given our results suggesting that a number of peripheral RGCs, including 22% of iRGCs, are generated in the CMZ and that their generation depends on Cyclin D2, we asked whether Cyclin D2 expression is compromised in the albino and therefore linked to the reduction of iRGCs.…”
Section: Resultsmentioning
confidence: 99%
“…This phenotype is associated with mutations in melanin production or melanosome biogenesis and turnover, and leads to decussation defects and mistargeting (Rice et al, 1995, Herrera et al, 2003, Rebsam et al, 2012, Bhansali et al, 2014, Jeffery, 2001). Birthdating experiments have suggested that this is due to a delay in the generation of RGCs in albino compared with pigmented retina (Bhansali et al, 2014, Drager, 1985, Gimenez et al, 2005, Lavado et al, 2006, Rachel et al, 2002). Given our results suggesting that a number of peripheral RGCs, including 22% of iRGCs, are generated in the CMZ and that their generation depends on Cyclin D2, we asked whether Cyclin D2 expression is compromised in the albino and therefore linked to the reduction of iRGCs.…”
Section: Resultsmentioning
confidence: 99%
“…The section containing the optic nerve head was identified and the sections retained directly above and below were used. Five individuals and both eyes were used per group resulting in n = 20 measurements, as described (Gimenez et al . 2005).…”
Section: Methodsmentioning
confidence: 99%
“…Outer segments counts were undertaken on 1–2 mm Historesin sections in each of the groups as described (Jeffery et al . 1997; Gimenez et al . 2005).…”
Section: Methodsmentioning
confidence: 99%
“…The highly specialised RPE plays a key role in regulating retinal development (Raymond and Jackson, 1995;Martínez-Morales et al, 2004;Gimé nez et al, 2005). Moreover, RPE-derived cells display several properties of neural progenitor cells: (i) neural progenitor identity, based on the expression of markers used to identify neural stem and progenitor cells; (ii) proliferation with limited self-renewal; (iii) and differentiation into neuronal and glial cells based on the expression of differentiation markers (Reh and Levine, 1998;Seaberg and van der Kooy, 2003).…”
Section: Pcna In the Retinal Pigment Epitheliummentioning
confidence: 99%